User's view on information security in government sector / Siti Asmah Ibrahim - Ibrahim, Siti Asmah (2015)
Information has become a main concern to be secured for organizations as technology grows changing rapidly in our global society People and technology are link. Employees are dealing with information technology in their routine and daily task. When employees' put a good efforts and combining it with the technology, organizations can be more successful. Employees need to understand their role that relates to the information security in performing their daily job. The key successes of information security rely on appropriate information security practice behaviours by the end users. Further, there is often conflict with exactly how a specific implementation of security practices that associated impact on workplace practices. Therefore, this research is to provide overall view on users' experience of information security in their individual role in order to ensure the success and efficiencies information security practices in the government sector. The research approach was using the qualitative method. The data was analysed to understand the view of users' experience of information security in their individual job. The results of the study also suggested that a holistic strategic to ensure the success and efficiencies information security practices in the government sector. It is hope that the study can contribute to the improvement of user's awareness and knowledge about the important of information security.